2017
DOI: 10.1186/s13059-017-1281-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered chromatin compaction and histone methylation drive non-additive gene expression in an interspecific Arabidopsis hybrid

Abstract: BackgroundThe merging of two diverged genomes can result in hybrid offspring that phenotypically differ greatly from both parents. In plants, interspecific hybridization plays important roles in evolution and speciation. In addition, many agricultural and horticultural species are derived from interspecific hybridization. However, the detailed mechanisms responsible for non-additive phenotypic novelty in hybrids remain elusive.ResultsIn an interspecific hybrid between Arabidopsis thaliana and A. lyrata, the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
108
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 111 publications
(123 reference statements)
9
108
0
Order By: Relevance
“…This suggests differential epigenetic modifications between two subgenomes within the allotetraploid, which is consistent with genome-wide dominance of A. arenosa genes over A. thaliana ones [61••]. A recent study in the interspecific hybrid between A. thaliana and A. lyrata also found overall down-regulation of A. thaliana genes compared to A. lyrata genes, which correlates with A. thaliana chromatin that is more compact than A. lyrata chromatin [83], and the A. thaliana genes that are associated with histone H3K27me3 marks tend to alter their expression in the interspecific hybrid.…”
Section: Nonadditive Gene Expression and Epigenetic Regulation In Intsupporting
confidence: 55%
“…This suggests differential epigenetic modifications between two subgenomes within the allotetraploid, which is consistent with genome-wide dominance of A. arenosa genes over A. thaliana ones [61••]. A recent study in the interspecific hybrid between A. thaliana and A. lyrata also found overall down-regulation of A. thaliana genes compared to A. lyrata genes, which correlates with A. thaliana chromatin that is more compact than A. lyrata chromatin [83], and the A. thaliana genes that are associated with histone H3K27me3 marks tend to alter their expression in the interspecific hybrid.…”
Section: Nonadditive Gene Expression and Epigenetic Regulation In Intsupporting
confidence: 55%
“…Collectively, our results suggest that although histone modification (H3K4me3 and H3K27me3) remodeling contributes to the overall non‐additive gene expression in rice F 1 hybrids, DNA methylation does not seem to play a major role. This is consistent with recent findings in Arabidopsis intra‐ and interspecific F 1 hybrids that DNA methylation remodeling does not directly impact gene expression (Greaves et al ., ; Zhu et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Gene expression in an F 1 hybrid is regulated by the independent actions, as well as interactions, of its subgenomes. Epiallelic interactions and remodeling may play a major role in orchestrating the unique gene expression profile of a hybrid (Groszmann et al ., ; Shi et al ., ; Zhang et al ., ; Zhu et al ., ; Ding and Chen, ). We profiled transcriptomes in leaf and root of the reciprocal F 1 hybrids and their parent cultivars (NPB and 93‐11).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A second key result of this study is that, notwithstanding the overall methylome stability among the genomically divergent and recombinant allopolyploid rice lines, locus‐specific DNA methylation repatterning occurred extensively, and that this effect appears to be caused by the combination of WGD and HEs, rather than by hybridization per se. In this aspect, we note that several previous studies in a wide spectrum of plant taxa including A. thaliana (Greaves et al ., ; Yang et al ., ; Zhu et al ., ), rice (He et al ., ; Chodavarapu et al ., ; Zhao & Zhou, ; Chen & Zhou, ) and maize (Springer & Stupar, ; Zhao et al ., ) have shown that DNA methylation may undergo extensive repatterning in F1 hybrids. However, our results indicate that the effect of hybridization on DNA methylation alteration pales when compared with that of WGD and HEs.…”
Section: Discussionmentioning
confidence: 99%